TELAAH TERHADAP PEMBATASAN LINGKUP AHLI WARIS PENGGANTI PASAL 185 KHI OLEH RAKERNAS MAHKAMAH AGUNG RI DI BALIKPAPAN OKTOBER 2010 - Ahmad Zahari (Jurnal Dinamika Hukum, 2014)
Article 185 of KHI on substitute heirs which was basically bilateral has been directed to the patrilineal inheritance law. Consequently, the position and rights of substitute heirs have become uncertain depending on the other heirs’ mercy or the judge. The polemic of its interpretation has caused justice uncertainty. The meeting between the Supreme Court and the four appellate courts held in Balikpapan on 10-14 October 2010, instead of being expected to provide solution to the problem, has in fact restricted the scope of the substitution to the level of grandchildren. Consequently, the arrangement for other substitute heirs has become absurd and uncertain.Keywords: Islamic law Compilation, restriction of substitute heirs, heirs system